Comments on "Sluggish diffusion in Co–Cr–Fe–Mn–Ni high-entropy alloys" by K.Y. Tsai, M.H. Tsai and J.W. Yeh, Acta Materialia 61 (2013) 4887–4897. (1st July 2017) - Paul, Aloke
Abstract: The wrong estimation of the diffusion coefficients following the quasi-binary approach and subsequent analysis by Tsai et al. in Co-Cr-Fe-Mn-Ni high entropy alloy are explained. Since this approach, formulated by the present author before the publication by Tsai et al., has potential to emerge as an efficient technique in multicomponent systems, the correct steps of estimation of the diffusion coefficients are explained in detail. At present state, the diffusion data reported in high entropy alloy Tsai et al. has no significance unless estimated again following the correct steps.